Tailor-Made High Density PLA Foam Sheets - Strategies to Improve the Mechanical Properties. Issue 5 (September 2014) - Geissler, Bernd; Feuchter, Michael; Laske, Stephan; Walluch, Matthias; Holzer, Clemens; Langecker, Günter R.
In this study, different strategies to improve the mechanical properties of physically foamed high density polylactic acid (PLA) sheets were examined to produce PLA foam sheets with tailor-made mechanical properties. The first part was the determination of the influence of the blending of PLA with polybutylene succinate (PBS) on the properties of the high density foam sheets. Additionally, the influence of the PBS on the rheological properties was investigated with a cone plate rheometer. The second part was to manufacture multilayer films with a physically foamed middle layer and highly filled skin layers. The foamed sheets were characterized in terms of mean cell size, cell density, density and surface roughness. The experiments were carried out on lab scale multi-layer extrusion line.